Uma proposta de tratamento dos dados sobre acidentes nas rodovias federais brasileiras com vistas a atuar preventivamente na redução de sua ocorrência - Ferreira, Paulo César Pêgas (2017)
This thesis aims to present a study on the development of a methodology for the analysis and prediction of the quantity and severity of traffic accidents in Brazil, based on the occurrences recorded by the Federal Highway Police on Brazilian federal highways during 2009, from the mathematic treatment of the related factors, in the case the AADT (Annual Average Daily Traffic) by lane and urban and / or rural range and / or extension of the stretches. In addition, criteria for parameterization of the severity of accidents was used, to identify the opportunity to use them to identify the segments with the highest concentration of occurrences, based on their social costs. This set of information was worked from software with the use of data processing tools, with the purpose of arriving at mathematical models that allowed to define the relationships of the factors of greater relevance, in the analysed sections. Geospatial studies were incorporated that will allow not only the geographic location of the stretches but also their confrontation with socioeconomic information, to understand if there is a direct correlation between these indicators in the Regions, States and Metropolitan Regions of Brazil.